James Willis Robb, Patterns of image and structure in the essays of Alfonso Reyes. Abstract of a dissertation. The Catholic University of America Press, Washington, D. C., 1958; 92 pp. (Studies in Romance Languages and Literatures, 66). - Mejía Sánchez, Ernesto (Nueva Revista de Filología Hispánica (NRFH), 1958)
Se reseñó el libro: Patterns of image and structure in the essays of Alfonso Reyes.